2017
DOI: 10.4300/jgme-d-17-00304.1
|View full text |Cite
|
Sign up to set email alerts
|

Straight Line Scoring by Clinical Competency Committees Using Emergency Medicine Milestones

Abstract: Most programs did not submit SLS ratings. Because of the statistical improbability of SLS, any SLS ratings reduce the validity assertions of the milestone assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 4 publications
(6 reference statements)
1
25
0
Order By: Relevance
“…10 Therefore, we chose to focus our initial analysis on data from 3 of the phase 1 specialties—emergency medicine (EM), diagnostic radiology (DR), and urology (UR)—because of the consistency in the milestone reporting protocol between these specialties and to build on early published validity research of milestone ratings. 1114…”
Section: Methodsmentioning
confidence: 99%
“…10 Therefore, we chose to focus our initial analysis on data from 3 of the phase 1 specialties—emergency medicine (EM), diagnostic radiology (DR), and urology (UR)—because of the consistency in the milestone reporting protocol between these specialties and to build on early published validity research of milestone ratings. 1114…”
Section: Methodsmentioning
confidence: 99%
“…While milestones have moved us towards CBME in the U.S., the assessment of individual milestones has proven difficult, as evidenced by more programs than expected submitting straight-line scoring 33,34. This may be due to assessors having difficulty translating the level of trust they have for a trainee to perform a specific work-based activity into the multiple requisite competency domains.…”
Section: Discussionmentioning
confidence: 99%
“…Beeson et al 2 found that this arose in only about 6% of all assessments. However, it was not evenly distributed across programs, with 4% of programs submitting more than 50% of their assessments with SLS.…”
Section: In This Issue Of the Journal Of Graduate Medical Educationmentioning
confidence: 95%
“…Cooper 1 reviewed a number of potential causes, although he does not estimate the relative contribution of each. Undersampling reflects an inadequate number of observations, which may well apply in the context of firsttime ratings as suggested by Beeson et al 2 Engulfing occurs when ratings of individual attributes are influenced by an overall impression. Beeson et al 2 propose that the final ratings of graduating residents may have been a result of this phenomenon, where the score was linked to predicted success of graduation.…”
Section: In This Issue Of the Journal Of Graduate Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation